CUSTOMER PERCEPTION ANALYSIS ON PRODUCT BRAND IMAGE OF ROLAND KEYBOARD IN MANADO - Watung, Irene I.; Pangemanan, Sifrid S.; Tielung, Maria V. J. (Universitas Sam Ratulangi, 2021)
Customer Assessment analysis on Product Brand Image: Case of Roland Keyboard in Manadoâ€. Brand image is considered as one of the critical factors, which enables a company to be beneficial or disastrous. The way for interpreting its success or not depends on how the customers will look it. Keyboard is one of the major products that is usually used in music it is always improving based on technology development and customer satisfaction. Roland Keyboard is one of the musical products that has been used by Manado Society and of course has its customer assessments of this product.Â Keywords: Product brand image, keyboard brand, customer perception